Genotyping of viable Toxoplasma gondii from the first national survey of feral swine revealed evidence for sylvatic transmission cycle, and presence of highly virulent parasite genotypes. Issue 3 (11th March 2020) - Dubey, J. P.; Cerqueira-Cézar, C. K.; Murata, F. H. A.; Verma, S. K.; Kwok, O. C. H.; Pedersen, K.; Rosenthal, B. M.; Su, C.
Abstract: Feral swine are known reservoirs of various pathogens, including Toxoplasma gondii . Here, we report the first national survey of viable T. gondii in feral swine in the USA. We paired serological surveys with parasite isolation and bioassay to evaluate the prevalence and genetic diversity of these parasites. From 2012–2017, sera and tissues from 1517 feral swine across the USA were collected for the isolation of viable T. gondii. Serum samples were initially screened for antibodies to T. gondii, and then the tissues of seropositive feral swine were bioassayed in mice. Antibodies were detected in 27.7% of feral swine tested by the modified agglutination test (1:25 or higher). Antibody positive rates increased significantly with age, with 10.1% of juveniles, 16.0% of sub-adults and 38.4% of adults testing seropositive. Myocardium (50 g) from 232 seropositive feral swine was digested in pepsin and bioassayed in mice. Viable T. gondii was isolated from 78 feral swine from 21 states. Twelve of the 78 isolates were pathogenic to outbred Swiss Webster mice and 76 of the 78 isolates could be propagated further in cell culture and were genotyped. For genotyping, deoxyribonucleic acid extracted from cell culture-derived tachyzoites was characterized by polymerase chain reaction restriction fragment length polymorphism using the genetic markers SAG1, SAG2, SAG3, BTUB, GRA6, c22-8, c29-2, L358, PK1 and Apico. Genotyping revealed 15 ToxoDB genotypes, including 43 isolates for genotype #5 (haplogroup 12), 11 isolates for #24, four isolates for #2 (haplogroup 3), two isolates for each of genotypes #3 (haplogroup 2), #4 (haplogroup 12), #216, #221, #289 and #297 and one isolate for each of genotypes #1 (haplogroup 2), #39, #66, #260, #261 and #299. Genotype #5 was the most frequently isolated, accounted for 57% (43/76) of the isolates, followed by #24, accounted for 14% (11/76). Genotypes #260, #289, #297 and #299 are new types. Genotype #289 was highly virulent to mice and originated from feral swine collected in Louisiana on the same day at the same location. Genotype #216 was previously demonstrated to be highly virulent to mice. Our results indicate moderate genetic diversity of T. gondii in feral swine in the USA, with the genotype #5 (haplogroup 12) dominant in the continental USA, whereas genotype #24 (10/14) was dominant in Hawaii, suggesting different population structures of the parasites among the two distinct geographical locations.